2018
DOI: 10.1016/j.physbeh.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental temperature deception on perceived exertion during fixed-intensity exercise in the heat in trained-cyclists

Abstract: Participants were under the impression they were cycling in different environments; however, this did not influence RPE. These data suggest that for trained cyclists, an awareness of environmental temperature does not contribute to the generation of RPE when exercising at a fixed intensity in the heat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Indeed, the intensity of perception of effort during a motor task has been extensively shown to be responsive to changes in task difficulty imposed by various experimental manipulations. As an example, the perception of effort is altered by the intensity of muscle contraction (e.g., de Morree and Marcora, 2010 , 2012 ), the presence of muscle or mental fatigue (e.g., Pageaux and Lepers, 2016 , 2018 ; Jacquet et al, 2021 ), or changes in environmental conditions (e.g., Girard and Racinais, 2014 ; Borg et al, 2018 ; Jeffries et al, 2019 ). In our study, to test the possibility to monitor the exercise intensity during upper-limb motor tasks, we altered task difficulty by manipulating the physical demand of the tasks performed via imposing various movement tempos or adding weights on the forearm.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the intensity of perception of effort during a motor task has been extensively shown to be responsive to changes in task difficulty imposed by various experimental manipulations. As an example, the perception of effort is altered by the intensity of muscle contraction (e.g., de Morree and Marcora, 2010 , 2012 ), the presence of muscle or mental fatigue (e.g., Pageaux and Lepers, 2016 , 2018 ; Jacquet et al, 2021 ), or changes in environmental conditions (e.g., Girard and Racinais, 2014 ; Borg et al, 2018 ; Jeffries et al, 2019 ). In our study, to test the possibility to monitor the exercise intensity during upper-limb motor tasks, we altered task difficulty by manipulating the physical demand of the tasks performed via imposing various movement tempos or adding weights on the forearm.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the intensity of perception of effort during a motor task has been extensively shown to be responsive to changes in task difficulty imposed by various experimental manipulations. As an example, perception of effort is altered by the intensity of muscle contraction (e.g., de Morree & Marcora, 2010, the presence of muscle or mental fatigue (e.g., Jacquet et al, 2021;Pageaux & Lepers, 2016;Pageaux & Lepers, 2018) or changes in environmental conditions (e.g., Borg et al, 2018;Girard & Racinais, 2014;Jeffries et al, 2019). In our study, to test the possibility to monitor the exercise intensity during upper-limb motor tasks, we altered task difficulty by manipulating the physical demand of the tasks performed via imposing various movement tempos or adding weight on the forearm.…”
Section: Perception Of Effort Changes With the Manipulation Of Physical Demandmentioning
confidence: 99%
“…For instance, the strength of the connection between AEI and RPE may be influenced by individuals’ intrapersonal variables, because RPE is a developing phenomenon that improves through developmental time in lockstep with overall cognitive growth [ 36 ]. Second, prior research has indicated that OW and OB people sweat more than normal weight (NW) people at the same temperature and intensity [ 46 ], limiting their capacity to properly assess their AEI [ 47 ]. Third, it is anticipated that AEI connections may grow stronger with age and body mass index (BMI) [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, prior research has indicated that OW and OB people sweat more than normal weight (NW) people at the same temperature and intensity [ 46 ], limiting their capacity to properly assess their AEI [ 47 ]. Third, it is anticipated that AEI connections may grow stronger with age and body mass index (BMI) [ 46 ]. Fourth, the strength of the connection between AEI and RPE may depend on how AEI (e.g., exercise modalities, surroundings, and protocols) and RPE are operationalized (e.g., test time and measurement of the perceived exertion scale).…”
Section: Introductionmentioning
confidence: 99%